2012
DOI: 10.1097/mrr.0b013e3283508e2e
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude regarding recovery among mental health practitioners in Sweden

Abstract: The aim was to investigate the knowledge and the attitude regarding recovery among practitioners working in the Swedish mental health system, Personligt Ombud (PO), Supported Housing Team (SHT) and Psychiatric Out Patient Service (POPS), to determine whether and how knowledge and attitude regarding recovery differ between the three services. A web-based questionnaire based on the Recovery Knowledge Inventory was sent to the participants. Participant selection ensured that different parts of Sweden were represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…A study reported that health professionals with experience in mental illness had significantly less variation in their knowledge score compared with those without experience (Doughty et al 2008). However, Klockmo et al (2012) reported otherwise. Regarding profession, Hardiman and Hodges (2008) reported that psychologists were less likely to be familiar with the recovery literature compared with other professionals (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported that health professionals with experience in mental illness had significantly less variation in their knowledge score compared with those without experience (Doughty et al 2008). However, Klockmo et al (2012) reported otherwise. Regarding profession, Hardiman and Hodges (2008) reported that psychologists were less likely to be familiar with the recovery literature compared with other professionals (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the others reported on cohort studies aimed at following up the extent of recovery in severe mental illness (Arvidsson, 2011;Lauronen et al, 2005), and one reported on a questionnaire study assessing recovery-oriented attitudes of three personnel groups involved in service provision (Klockmo et al, 2012). No position papers or literature reviews were found.…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of the qualitative studies, diagnosis was self-reported. One study focused on staff in mental health services (Klockmo et al, 2012) and one on a combination of both staff and patients (Färdig et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations